The School Literacy Movement Program During a Pandemic: Countenance Stake Model - Shendi Kharisma Widiastuti; Iriani, Ade; Wasitohadi (Universitas Pendidikan Ganesha, 2023)
Literacy activities are one of the government's efforts to increase the potential and quality of student education, including through the School Literacy Movement (GLS) program. This program is relevant to enacting the abolition of the national exam and passing a minimum competency assessment. As of 2019, the literacy rate for children in Indonesia is 42 out of 49 countries. It was exacerbated by the COVID-19 pandemic, which disrupted schools' teaching and learning processes. The purpose of this study is to evaluate the implementation of the GLS. This type of research is descriptive qualitative research with a countenance stake evaluation model. Triangulation uses method triangulation in the form of interviews and observations and source triangulation in the form of school principals, teachers, librarians, and parents. Data analysis uses 3 stages: data reduction, presentation, and conclusion/verification. The study's results are that the overall evaluation results are excellent. The output of literacy in the form of increasing students' language ability has increased, such as reading fluently, using punctuation marks correctly, providing responses, and making up stories. In addition, students' skills also increase and are shown by the existence of works in the form of published writings.